The complete mitochondrial genome of Sarcophaga brevicornis (Diptera: Sarcophagidae) - Changquan Zhang; Wang Shiwen; Yanjie Shang; Xiao Shen; Yadong Guo (Mitochondrial DNA. Part B. Resources, 2019)
Sarcophaga brevicornis (Diptera: Sarcophagidae) was of utmost forensic importance due to their wide distribution, ubiquitous, and synanthropic nature. The complete mitochondrial genome (mitogenome) of S. brevicornis was first sequenced and assembled in this study. The length of circular mitogenome was 15,152 bp, which showed in a typical arthropod genome, including 13 protein-coding genes (13 PCGs), two ribosomal RNA (two rRNA) genes, 22 transfer RNA (22 tRNA) genes, and an AT-rich region. Its nucleotide composition was A 39.0%, C 12.7%, G 10.6%, and T 37.7%. Furthermore, phylogenetic relationships of S. brevicornis and the published sarcophagid species were evaluated based on 13 PCGs. The results indicated that S. brevicornis was clearly separated from the other sarcophagid species, but it was closed to the species of Sarcophaga similis. This study provided a significant database reference for genetic structure and phylogenetic analysis of Sarcophagidae.